2008
DOI: 10.1080/15402000801952914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Call on Sleep and Mood in Internal Medicine Residents

Abstract: Residents on call experience decreased total sleep time (TST) and increased dysphoria. This study monitored changes in mood and sleepiness for 3 post-call days. Fifty-two internal medicine residents participated in the study. The residents wore actigraphs for the 4 to 9 days of the study. Each morning resident completed mood scales, a sleepiness scale, and estimated their prior night TST. The residents were on a 1-in-4 schedule. Call decreased subjective- and actigraphy-derived TST to less than 4 hr. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Neurocognitive effects of resident and faculty physician sleep deprivation have been shown in many small studies including effects on fine motor skills,10 simulated surgical skills,11 psychomotor vigilance3 10 12–14 and a variety of cognitive outcomes 1–3 14–17. One resident study demonstrated prolonged neurobehavioural effects of sleep deprivation past the first night of recovery sleep after call shifts, suggesting that inadequate sleep was not recouped by one night of sleep postcall 18. This requires further study in larger studies examining overnight call in physicians and night shifts to see if adequate sleep prior to starting 24-hour call duties, or night shifts may help in minimising cognitive effects of physician sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive effects of resident and faculty physician sleep deprivation have been shown in many small studies including effects on fine motor skills,10 simulated surgical skills,11 psychomotor vigilance3 10 12–14 and a variety of cognitive outcomes 1–3 14–17. One resident study demonstrated prolonged neurobehavioural effects of sleep deprivation past the first night of recovery sleep after call shifts, suggesting that inadequate sleep was not recouped by one night of sleep postcall 18. This requires further study in larger studies examining overnight call in physicians and night shifts to see if adequate sleep prior to starting 24-hour call duties, or night shifts may help in minimising cognitive effects of physician sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Sleep, depression, and anxiety: emerging associations with technology use It is well documented that poor sleep quality is related to higher levels of depression. 20,21 According to the ACHA-NCHA, 22 12 percent of students reported experiencing depression during their college years. Even more college students (19 percent) have been diagnosed with anxiety disorders during their college years.…”
Section: Introductionmentioning
confidence: 98%
“…The average score was 12.2 ± 4.6 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] placing them within the normal range for their age and sex according to norms [26]. Therefore, pre-study PSS-10 scores indicate that the participants were not a high-stress group.…”
Section: Discussionmentioning
confidence: 99%
“…This is well supported in the literature, particularly the medical industry, where it is not uncommon to see sleep durations \2-4 h across on-call duty periods (e.g. [3][4][5]). Similar patterns have been observed in other industries, with ship engineers in one study taking approximately 32 min to action each alarm during on-call nights and as a result, experienced significantly shorter sleep [12].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation